Forms and Functions of the Social Emotions. (August 2021) - Sznycer, Daniel; Sell, Aaron; Lieberman, Debra
In engineering, form follows function. It is therefore difficult to understand an engineered object if one does not examine it in light of its function. Just as understanding the structure of a lock requires understanding the desire to secure valuables, understanding structures engineered by natural selection, including emotion systems, requires hypotheses about adaptive function. Social emotions reliably solved adaptive problems of human sociality. A central function of these emotions appears to be the recalibration of social evaluations in the minds of self and others. For example, the anger system functions to incentivize another individual to value your welfare more highly when you deem the current valuation insufficient; gratitude functions to consolidate a cooperative relationship with another individual when there are indications that the other values your welfare; shame functions to minimize the spread of discrediting information about yourself and the threat of being devalued by others; and pride functions to capitalize on opportunities to become more highly valued by others. Using the lens of social valuation, researchers are now mapping these and other social emotions at a rapid pace, finding striking regularities across industrial and small-scale societies and throughout history.